Matkovska I. V., Makarenko Y. G. The comparative aspect of lexico-semantic translation peculiarities of author`s nominations in fantasy - Matkovska I. V.; Makarenko Y. G. (Philological Treatises, 2020)
The article considers the principles of the translation of different language units with fantastic semantics in a fantasy novel. It presents the comparative analysis of the approaches to the translation of the fantasy-colored lexemes on the basis of Ukrainian and Russian translations of the novels by J. K. Rowling.